СТРУКТУРА РУСЛОВОГО РЕЛЬЕФА НИЖНЕЙ ВОЛГИ - Сидорчук А.Ю. (My University, 2005)
The hierarchical classification of Lower Volga channel landforms is put forward. The classification consists of 8 complexes and 5 classes. The class of nanoforms includes riffles; microforms - dunes and zastrugas; mezoforms -sand waves and alternate bars; macroforms - big meanders and large ramification junctions; megaforms - ramifica-tions with parallel arms or the river. The main channel of Volga and its branch - Akhtuba form a parallel-channel system. Empirical probability density of channel forms length (for each class) may be fitted well by Gamma distribu-tion; the height may by fitted by Weibull distribution.
Keywords: 551.435.11(282.247.41)